Evaluation of a Computer‐aided Lung Auscultation System for Diagnosis of Bovine Respiratory Disease in Feedlot Cattle. (8th June 2015) - Mang, A.V.; Buczinski, S.; Booker, C.W.; Timsit, E.
<x xml:space="preserve">Abstract</x> Background A computer‐aided lung auscultation (CALA) system was recently developed to diagnose bovine respiratory disease (BRD) in feedlot cattle. Objectives To determine, in a case–control study, the level of agreement between CALA and veterinary lung auscultation and to evaluate the sensitivity (Se) and specificity (Sp) of CALA to diagnose BRD in feedlot cattle. Animals A total of 561 Angus cross‐steers (initial body weight = 246 ± 45 kg) were observed during the first 50 day after entry to a feedlot. Methods Case–control study. Steers with visual signs of BRD identified by pen checkers were examined by a veterinarian, including lung auscultation using a conventional stethoscope and CALA that produced a lung score from 1 (normal) to 5 (chronic). For each steer examined for BRD, 1 apparently healthy steer was selected as control and similarly examined. Agreement between CALA and veterinary auscultation was assessed by kappa statistic. CALA's Se and Sp were estimated using Bayesian latent class analysis. Results Of the 561 steers, 35 were identified with visual signs of BRD and 35 were selected as controls. Comparison of veterinary auscultation and CALA (using a CALA score ≥2 as a cut off) revealed a substantial agreement (kappa = 0.77). Using latent class analysis, CALA had a relatively high Se (92.9%; 95% credible interval [CI] = 0.71–0.99) and Sp (89.6%; 95% CI = 0.64–0.99) for diagnosing BRD compared with pen checking. Conclusions CALA had good diagnostic accuracy (albeit with a relatively wide CI). Its use in feedlots could increase the proportion of cattle accurately diagnosed with BRD.